RESPON MASYARAKAT TERHADAP PELAYANAN KELURAHAN REJOSARI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Rizki Abdia Fernanda; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
This study aims to determine the community's response to the services of the Rejosari village, the services provided will certainly provide various kinds of responses, the responses here are divided into 3 types of responses, namely, Cognitive, Affective, and Psychometric Responses. The response is measured through the services provided with 5 types of service aspects, namely, physical condition, reliability, responsiveness, certainty, and empathy. This research was conducted in Rejosari Village, Tenayan Raya District, Pekanbaru City. To obtain the results of this study the authors used descriptive quantitative methods with the number of respondents 93 people. The results of this study showed that the community's response to services in Rejosari Village was in the